LER, ESCREVER E CONTAR: ESCOLAS INFORMAIS DO FAXINAL DOS MARMELEIROS ENTRE OS ANOS DE 1930 E 1949 - Pereira, Jacieli Domingues (2014)
This dissertation aims to understand the function and importance of education in the Faxinal Marmeleiros community, located inner city of Rebouças - Paraná, at a time when no formal schooling was still present ( 1930`s and 1940`s ) . The fact that no had schools subsidized by the government did not prevent many faxinalenses had access to education. The first schools were established and organized by the residents themselves, and those who could and wanted banded together to neighbors and paid for a teacher at their children. Through interviews conducted with the faxinalenses in the form of recorded interviews , we seek to answer the following questions: Why , in an eminently rural community , almost insulated from the nearest urban centers , have as much concern about teaching ( reading and also writing and " accounts " ) for children about to expend sums of money for such a purpose? What led parents (often illiterate) to wish that their children had access to education, as his most likely destination would work on the farm? Is used, so the methodological contribution of oral history in their eagerness to understand the daily life of the school faxinalenses as well as assumed by education in that community function. It also refers to official documents of the time in order to rebuild the educational setting off faxinal at the national and state levels. The clash of these two types of sources can trace the main features of education accessed by residents of faxinal historical subjects, highlighting its characteristics and outlining the differences towards institutionalized education offered by the government. About to the theoretical precepts , if dialogue mainly with Michel de Certeau the perspective of History of Everyday Life , through application of the key concepts of this author, namely: " Tactics " , " strategies " , " convenience " , " space " and " place ".